Health effects of parental deaths among adults in Norway: Purchases of prescription medicine before and after bereavement. (December 2016) - Kravdal, Øystein; Grundy, Emily
Abstract: We analyse effects of parental deaths on the health of women and men aged 18–59 in 2004–2008, indicated by purchases of prescription medicines. Register data covering the entire Norwegian population were used, and fixed-effects models were estimated to control for unobserved time-invariant individual factors. A parent's death seemed to have immediate adverse consequences in both main age groups considered (18–39, 40–59), although effects were lower in the older group. Some results suggested that this health disadvantage widened with increasing time since the parent's death. However, effects were weak: the annual number of different medicines purchased was only increased by 1–7% as a result of losing a parent. Death of a parent was associated with an immediate increase in purchases of medication for mental diseases, and there were indications of a physical response as well. As time since the parental death increased, there was a decline in the purchase of medication for mental diseases, but an opposite trend with respect to medication for other diseases. On the whole, maternal and paternal deaths had the same impact, and effects on daughters and sons were of the same magnitude. Highlights: A parent's death seemed to have immediate weakly adverse health consequences. Some results suggested that this health disadvantage widened with time since death. The effects on physical and mental health seemed to be different. Purchases of prescription medicine were used as indicators of health. Unobserved time-invariant individual factors were controlled for.